On some approximations and main topological descriptions for special classes of Banach spaces with integrable derivatives - Melnik, V.; Kasyanov, P.; Piccirillo, A. M. (Methods of Functional Analysis and Topology, 2008)
We consider some classes of Banach spaces with integrable derivatives. An important compactness lemma for nonreflexive spaces is obtained. However some main topological properties for the given spaces are obtained.